SP1.1.14Future Insights on Virtual Reality Potential Uses as a Care Package for Colorectal Patients. (28th October 2021) - Gendia, A; Rottenburg, H; Hutton, M; Cota, A; Clark, J
Abstract: Aim: To provide an insight on current applications of immersive virtual reality (VR) on patients undergoing surgery and to project the potential uses of these applications on colorectal population. Methods: A non-systematic literature search of PubMed using key subject "Virtual Reality and Surgery" to identify relative articles. On reviewing applications of VR in surgery we identified four main areas of interest: preoperative education, perioperative support, postoperative pain management and rehabilitation. Results: VR technology showed promising results in all three stages of patient's journey ; In pre-surgery, VR was used as a powerful educational tool for vascular patients. Intraoperatively, it showed promising results as a distraction method to relief stress and discomfort in patients undergoing colonoscopy and gynaecology procedures. Postoperatively, VR was utilized in pain management in orthopaedics, cardiothoracic populations with acceptable results. Moreover, physical rehabilitation showed a strong outlet of the technology due to its engaging properties. Conclusion: VR has been showing applicable benefits in different stages of patient's care undergoing surgery. With proper future development of Its applications, VR potentials in colorectal population could be numerous; education on stoma and type of surgery with help of 3D environment, distraction tool for colonoscopy screening and postoperative pain. In addition, VR could help with enhanced recovery inform of physical and mental rehabilitation. Future uses of VR in colorectal population could be a key in improving outcomes and overall satisfactions. However, formulated studies and validated applications should be tackled to apply the technology safely in the standard care of colorectal patients.